The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1111/j.1572-0241.2006.00848.x
|View full text |Cite
|
Sign up to set email alerts
|

The Evolving Role of Leptin and Adiponectin in Chronic Liver Diseases

Abstract: Leptin and adiponectin, the main metabolic products of adipose tissue, have been implicated in a wide spectrum of human diseases. Given the frequent presence of hepatic steatosis in several chronic liver diseases, there is currently increasing interest in the role of these adipokines in the development of hepatic steatosis and also in necroinflammation and fibrosis, mostly in patients with nonalcoholic fatty liver disease or chronic hepatitis C. According to experimental data, reduced adiponectin levels and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
130
0
7

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(141 citation statements)
references
References 135 publications
4
130
0
7
Order By: Relevance
“…Existing studies suggest hypoadiponectinemia in NAFLD enhances insulin resistance by decreasing hepatic insulin sensitivity [41] and increasing production of the inflammatory protein, tumor necrosis factor-α [42]. Hypoadiponectinemia may perpetuate hepatic fat accumulation through an influx of free fatty acids into the liver resulting in hepatic steatosis [42,43]. Japanese women with NAFLD, defined by ultrasound, and mean ALT level of 45 U/L had significantly lower adiponectin concentration compared to those without NAFLD (7.2 vs. 9.0 ug/mL, p <0.005) [26].…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies suggest hypoadiponectinemia in NAFLD enhances insulin resistance by decreasing hepatic insulin sensitivity [41] and increasing production of the inflammatory protein, tumor necrosis factor-α [42]. Hypoadiponectinemia may perpetuate hepatic fat accumulation through an influx of free fatty acids into the liver resulting in hepatic steatosis [42,43]. Japanese women with NAFLD, defined by ultrasound, and mean ALT level of 45 U/L had significantly lower adiponectin concentration compared to those without NAFLD (7.2 vs. 9.0 ug/mL, p <0.005) [26].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with MetS and/or T2DM have low circulating adiponectin levels [86,87] . These are also decreased in patients with NAFLD, possibly due to enhanced hepatic insulin resistance together with declined FA β-oxidation [88,89] . In contrast, recombinant adiponectin administration exerted protective effects against NAFLD in mice [90] .…”
Section: Mechanistic Implicationsmentioning
confidence: 99%
“…A higher value of leptin according to E Tsochatzis can enhance IR, increase the cellular pool of fatty acids, and lead to the formation of liver steatosis [31]. B.Mattioli demonstrated that leptin may enhance the production of proinflammatory cytokines, including TNF-α [32].…”
Section: Discussionmentioning
confidence: 99%